Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


y=a x^{2} +bx+c
y= x^{2} +bx
y=a x^{2} +c

Where a,b,c are real numbers and a \neq 0.

Just remember that quadratic equation always has the  x^{2}


(x-2)(x+2) =  x^{2} -4
(x+2)(x+2)= x^{2} +4x+4
2x(x+2)=2 x^{2} +4

I hope that helps... :)

0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts